2009
DOI: 10.1063/1.3216845
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength dependence of the damage threshold of inorganic materials under extreme-ultraviolet free-electron-laser irradiation

Abstract: We exposed bulk SiC and films of SiC and B4C to single 25 fs long free-electron-laser pulses with wavelengths between 13.5 and 32 nm. The materials are candidates for x-ray free-electron laser optics. We found that the threshold for surface-damage of the bulk SiC samples exceeds the fluence required for thermal melting at all wavelengths. The damage threshold of the film sample shows a strong wavelength dependence. For wavelengths of 13.5 and 21.7 nm, the damage threshold is equal to or exceeds the melting thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…We find a slightly lower damage threshold for multiple pulses. Similar to the trends observed in experiments at longer wavelengths [2], the damage threshold is somewhat higher for bulk materials than for thin (µm-thick) films. Unlike in the longer-wavelength experiments, we observed strong mechanical cracking in the materials, which may be due to the larger penetration depths of the hard x-rays.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We find a slightly lower damage threshold for multiple pulses. Similar to the trends observed in experiments at longer wavelengths [2], the damage threshold is somewhat higher for bulk materials than for thin (µm-thick) films. Unlike in the longer-wavelength experiments, we observed strong mechanical cracking in the materials, which may be due to the larger penetration depths of the hard x-rays.…”
Section: Discussionsupporting
confidence: 73%
“…We now compare the damage behavior observed on similar materials at lower photon energies at FLASH [2,3] with the present LCLS results. In both cases, we observed that the damage thresholds of bulk materials are somewhat above the melt threshold, whereas the damage threshold for films is below.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…At longer time scales, processes not included in the present model would have to be considered, such as vaporization [48], ablation in bulk solids (on nanoseconds time scales) [53][54][55] and even resolidification (100 ns time scales) [56].…”
Section: Simulations and Plasma Modelingmentioning
confidence: 99%
“…To determine the experimental damage thresholds of B 4 C and SiC materials, several experiments spanning the photon energy range from 38.7 eV to 830 eV (32 nm to 1.5 nm) have been performed at the LCLS and FLASH FEL facilities 15,16 . The results are summarized in Figure 4 below.…”
Section: Fel Damage Experimentsmentioning
confidence: 99%